2014 14th International Conference on Control, Automation and Systems (ICCAS 2014) 2014
DOI: 10.1109/iccas.2014.6987866
|View full text |Cite
|
Sign up to set email alerts
|

A quadrocopter automatic control contest as an example of interdisciplinary design education

Abstract: Unmanned aerial vehicles (UAVs) have many applications and quickly gain popularity with the availability of low-cost micro aerial vehicles (MAVs). Robotics is a popular interdisciplinary education target as it involves understanding and collaboration of several disciplines. Thus, UAVs can serve as an ideal study platform. However, as robotics requires technical background, skills and initial efforts, it is commonly applied in long-term courses. In this paper we successfully exploit the opposite case of robotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 21 publications
(18 reference statements)
0
13
0
Order By: Relevance
“…(left) Co-located design, for a series of 9 NyARToolkit NyID markers. The optimal marker width ratio r w = 0.5 √ 5 − 1 ≈ 0.618 minimizes the size according to the constraint in (6). (right) Nested design, for a series of 5 markers, created using color-permutation.…”
Section: F Noise Removalmentioning
confidence: 99%
See 1 more Smart Citation
“…(left) Co-located design, for a series of 9 NyARToolkit NyID markers. The optimal marker width ratio r w = 0.5 √ 5 − 1 ≈ 0.618 minimizes the size according to the constraint in (6). (right) Nested design, for a series of 5 markers, created using color-permutation.…”
Section: F Noise Removalmentioning
confidence: 99%
“…The library has been successfully applied in a contest on autonomous drone navigation with students from different fields, where we found that a UAV can be a good educational tool to foster collaboration requiring multilateral perspectives (Sec. VII) [6]. This supports that robotics serves as a popular interdisciplinary education target, because making things move as intended involves understanding of several disciplines [7].…”
Section: Introductionmentioning
confidence: 98%
“…There are studies where the UAV recognizes the marker and controls the current position of the UAV [1]. There are also studies that utilize Simultaneous Localization and Mapping (SLAM) to create maps and locate positions [2].…”
Section: Introductionmentioning
confidence: 99%
“…For example, markers attached to walls are recognized by cameras on the UAV, and then the UAV is controlled autonomously by utilizing the recognized markers [11]. For autonomous flight, direction control and altitude control are required.…”
Section: Related Workmentioning
confidence: 99%